Two-Stage Bioconversion of Cellulose to Single-Cell Protein and Oil via a Cellulolytic Consortium - Eric Charles Peterson; Christian Hermansen; Ashriel Yong; Rowanne Siao; Gi Gi Chua; Sherilyn Ho; Coleen Toledo Busran; Megan Teo; Aaron Thong; Melanie Weingarten; Nic Lindley (Fermentation)
A novel approach for converting non-edible plant biomass into single-cell protein and oil (SCPO) via consolidated bioprocessing has been established, leveraging aerotolerant thermophilic cellulolytic consortia consisting mainly of Thermoanaerobacterium thermosaccharolyticum, Sporolactobacillus spp. and Clostridium sensu stricto to achieve the rapid and complete conversion of crystalline cellulose into a consistent cocktail of lactate, acetate and ethanol. This cocktail is an excellent substrate for cultivating organisms for SCPO production and food and feed applications, including Cyberlindnera jadinii, Yarrowia lipolytica and Corynebacterium glutamicum. Cultivation on this cocktail resulted in yields (YX/S) of up to 0.43 ± 0.012 g/g, indicating a yield from cellulose (YX/Cellulose) of up to 0.27 ± 0.007 g/g (dwb). The resulting SCPO was rich in protein (42.5% to 57.9%), essential amino acids (27.8% to 43.2%) and lipids (7.9% to 8.4%), with unsaturated fatty acid fractions of up to 89%. Unlike fermentation feedstocks derived from easily digested feedstocks (i.e., food waste), this approach has been applied to cellulosic biomass, and this mixed-culture bioconversion can be carried out without adding expensive enzymes. This two-stage cellulosic bioconversion can unlock non-edible plant biomass as an untapped feedstock for food and feed production, with the potential to strengthen resiliency and circularity in food systems.